Pengaruh Kemampuan Kerja, Pengalaman Kerja, dan Lingkungan Kerja terhadap Kinerja Pegawai (Studi pada Pegawai Bkkbn Provinsi Jawa Tengah) - Buana, Bintang Angkasa; Agus Prayitno; Sih Darmi Astuti; Awanis Linati Haziroh (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study analyzes the influence of work ability, work experience, and work environment on employee performance at the National Population and Family Planning Agency (BKKBN) Representative Office of Central Java Province. The population of this study was all employees working at the National Population and Family Planning Agency (BKKBN) of Central Java Province, with a sample of 100 respondents. The sampling technique used simple random sampling. The data source was primary data collected through questionnaires. Data analysis used multiple linear regression analysis. The results of the study showed that work ability had a significant positive effect on employee performance, work experience had a significant positive effect on employee performance, and the work environment had a significant positive effect on employee performance. The results of the determination coefficient showed that work ability, work experience, and work environment contributed 63.6 percent to the variance of employee performance variables, so further research is needed on other aspects of employee performance.   Keywords: Work Ability, Work Experience, Work Environment, Employee Performance